Induction of Cellular Deoxyribonuleic Acid Synthesis by Simian Virus 40 - Kit, Saul (1967)
The incorporation of (3)H-thymidine ((3)H-dT) into deoxyribonucleic acid (DNA) has been studied in uninfected confluent monolayer cultures of monkey kidney and mouse kidney cells, simian virus 40 (SV40)-infected cells, and in SV40-transformed mouse kidney cells. Radioautographic measurements revealed that during the period from 28 to 51 hr after productive SV40 infection of monkey kidney cultures about 80% of the cells synthesized DNA, compared to about 16% in uninfected cultures. At 28 to 43 hr after abortive SV40 infection of mouse kidney cultures, 24 to 37% of the cells synthesized DNA, compared to about 6 to 8% in uninfected cultures. The infected monkey kidney and mouse kidney cultures, respectively, incorporated about 5 to 10 times and 3 to 5 times as much (3)H-dT into DNA as did uninfected cultures. Moreover, the net DNA synthesized by SV40-infected monkey kidney cultures, estimated by colorimetric methods, substantially exceeded that of uninfected cultures. Nitrocellulose chromatography and band centrifugation experiments were performed to elucidate the kinds of DNA synthesized in the cultures. In uninfected monkey kidney cultures and at 2 to 12 hr after SV40 infection, almost all of the (3)H-dT labeled DNA sedimented more rapidly than SV40 DNA, and the radioactive DNA was denatured by heating for 12 min at 100 C (cellular DNA). Almost all of the labeled DNA obtained from abortively infected mouse kidney cultures and from SV40-transformed cells also had the properties of cellular DNA. However, approximately one-third to one-half of the labeled DNA obtained from monkey kidney cultures 28 to 51 hr after infection sedimented more slowly than cellular DNA and was not denatured by the heating (SV40 DNA). It is concluded that cellular DNA synthesis was induced during either the productive or abortive SV40 infections.